2020
DOI: 10.3390/ijms21082957
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide–Based Nanomaterials: An Insight into Retinal Prosthesis

Abstract: Retinal prosthesis has recently emerged as a treatment strategy for retinopathies, providing excellent assistance in the treatment of age-related macular degeneration (AMD) and retinitis pigmentosa. The potential application of graphene oxide (GO), a highly biocompatible nanomaterial with superior physicochemical properties, in the fabrication of electrodes for retinal prosthesis, is reviewed in this article. This review integrates insights from biological medicine and nanotechnology, with electronic and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 130 publications
(147 reference statements)
0
15
0
Order By: Relevance
“…Given this, a study showed that micropatterned graphene oxide (GO), when integrated with a retinal prosthesis, enabled the adhesion of retinal cells. In addition, GO-based nanomaterials provide enhanced safety, improved tissue regeneration, and repair [ 147 ]. Ranibizumab is an active humanized monoclonal antibody that neutralizes vascular endothelial growth factor A. Yan et al synthesized a formulation based on ranibizumab-conjugated iron oxide (Fe 3 O 4 )/PEGylated polylactide-co-glycolide (PEG-PLGA) for the treatment of neovascular age-related macular degeneration.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this, a study showed that micropatterned graphene oxide (GO), when integrated with a retinal prosthesis, enabled the adhesion of retinal cells. In addition, GO-based nanomaterials provide enhanced safety, improved tissue regeneration, and repair [ 147 ]. Ranibizumab is an active humanized monoclonal antibody that neutralizes vascular endothelial growth factor A. Yan et al synthesized a formulation based on ranibizumab-conjugated iron oxide (Fe 3 O 4 )/PEGylated polylactide-co-glycolide (PEG-PLGA) for the treatment of neovascular age-related macular degeneration.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Given this, a study showed that micropatterned graphene oxide (GO), when integrated with a retinal prosthesis, enabled the adhesion of retinal cells. In addition, GO-based nanomaterials provide enhanced safety, improved tissue regeneration, and repair [147]. Ranibizumab is an active humanized monoclonal antibody that neutralizes vascular endothelial growth factor A.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Despite all the promising results summarized in this article, there remain many hurdles to be resolved to enable successful restoration of vision. For example, not discussed in this article focusing on the visual acuity enhancement, proximate interfacing with the retinal tissue is another important issue of current retinal prostheses, thus newer materials such as conducting polymers, carbon nanotubes, and graphene oxide have been recently explored [205][206][207][208][209]. Future endeavors are expected to overcome the existing technological and physiological limitations.…”
Section: Other New Approachesmentioning
confidence: 99%
“…Such retinal stimulation methods that have been used to restore visual functions include electrical retinal prosthesis [ 4 , 9 , 10 ], optogenetics [ 11 ], photochemistry [ 12 ], ultrasonic stimulation [ 13 ], etc. Among them electrical stimulation based retinal prosthesis have been well studied for decades and recognized as the mainstream for practical applications [ 14 ]. In recent years, such retinal prostheses have achieved great progress in the device safety, integration and miniaturization, including microelectrode arrays, stimulator, wireless circuits, chip packaging, and implantation surgery [ 15 ].…”
Section: Introductionmentioning
confidence: 99%